Media Diplomacy in the Digital Age - Iriqat, Dalal S. (Journal of Ecohumanism, 2026)
Media diplomacy has become a defining feature of contemporary international relations, reshaping how states construct influence, legitimacy, and strategic positioning within an increasingly mediated global order. This article argues that media diplomacy is not merely an extension of traditional diplomatic practice but constitutes a distinct arena of power in which narratives, perceptions, and identities are actively constructed and contested. Drawing on theoretical frameworks of soft power, public diplomacy, mediatization, and network theory, the study examines how states deploy media strategically to influence global public opinion and geopolitical outcomes. Through case studies of Al Jazeera’s role in Qatar’s foreign policy and China’s digital diplomacy during the U.S.–China trade conflict, the article demonstrates that media operates simultaneously as an instrument of influence and a site of political struggle. It further explores structural limitations, including algorithmic mediation, information overload, credibility erosion, and technological disruption. The article concludes that the effectiveness of media diplomacy depends on the integration of communication strategy, technological adaptation, and normative legitimacy within a fragmented and contested global communication ecosystem.